2016
DOI: 10.1063/1.4941623
|View full text |Cite
|
Sign up to set email alerts
|

Metastable-stable phase transformation behavior of Al2O3 scale formed on Fe-Ni-Al alloys

Abstract: Abstract. The oxidation behavior of Ni-Fe-41.5Al alloy with different Fe/Ni ratio was investigated in air at 1000°C using in-situ high-temperature X-ray diffraction study by means of Synchrotron radiation. The oxidation mass gain of alloys decreased with increasing Fe content, particularly initial oxidation mass gain significantly decreased with increasing alloy Fe content. In-situ X-ray diffraction study indicated that the stable -Al 2 O 3 formed from beginning of oxidation on the alloy with higher Fe ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Fig. 4.9 shows the phase transformation behaviour of Al2O3 scale which formed on Fe-41.5Al (at.%), Ni-41Al-41Fe (at.%) and Ni-41.5Al (at.%) [44]. It was found that high iron content is beneficial and promotes the rapid transformation to α-Al2O3.…”
Section: Metastable and Stable Alumina Scale Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…Fig. 4.9 shows the phase transformation behaviour of Al2O3 scale which formed on Fe-41.5Al (at.%), Ni-41Al-41Fe (at.%) and Ni-41.5Al (at.%) [44]. It was found that high iron content is beneficial and promotes the rapid transformation to α-Al2O3.…”
Section: Metastable and Stable Alumina Scale Formationmentioning
confidence: 98%
“…From the previous studies, the template effect is interpreted as a precipitation of α-Al2O3 from the transient Fe2O3 with Al2O3 saturation [35,[40][41][42][43]. Hayashi et al [44] studied the meta-stable phase transformation behaviour of Al2O3 scale on Fe-Ni-Al alloys. They found that the oxidation mass gain tended to be reduced with the increased iron content in the alloy.…”
Section: Metastable and Stable Alumina Scale Formationmentioning
confidence: 99%